2012
DOI: 10.1177/1367006912454622
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of attitude on first language attrition and second language acquisition from a Dynamic Systems Theory perspective

Abstract: The factor attitude is generally considered to be among the most influential for first language (L1) attrition. Nevertheless, empirical validations have proven difficult to establish. While some studies could not find clear links between measures of attitude and L1 attrition (Hulsen, 2000; Yağmur, 1997), others showed that attitudes generated from exceptional life events strongly influenced attrition (Schmid, 2002) and that pragmatic vs. ideological motivation to emigrate and ensuing attitudes were clearly lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 27 publications
(45 reference statements)
2
29
0
7
Order By: Relevance
“…This hypothesis echoes the relationship between use and success observed in SLA. Secondly, and also in line with what has been found for SLA, it has often been predicted that attrition will be modulated by attitude and motivation, a more positive attitude toward the language itself and the speech community facilitating language maintenance (e.g., Cherciov, 2013). While both of these predictions may appear self-evident, empirical research to date has been strikingly unsuccessful in substantiating any such relationships (see Cherciov, 2011, 2013; Schmid, forthcoming for reviews) suggesting that, if there is an impact at all of exposure/use and attitude/motivation on L1At, it is much less pronounced and/or more complex than it is in SLA.…”
Section: Problems Of Measurementmentioning
confidence: 58%
See 1 more Smart Citation
“…This hypothesis echoes the relationship between use and success observed in SLA. Secondly, and also in line with what has been found for SLA, it has often been predicted that attrition will be modulated by attitude and motivation, a more positive attitude toward the language itself and the speech community facilitating language maintenance (e.g., Cherciov, 2013). While both of these predictions may appear self-evident, empirical research to date has been strikingly unsuccessful in substantiating any such relationships (see Cherciov, 2011, 2013; Schmid, forthcoming for reviews) suggesting that, if there is an impact at all of exposure/use and attitude/motivation on L1At, it is much less pronounced and/or more complex than it is in SLA.…”
Section: Problems Of Measurementmentioning
confidence: 58%
“…Opitz (2011) ascribes this hypothesised ‘trade-off’ in proficiency to the languages “competing for potentially insufficient resources required for maintaining the languages simultaneously at the desired high level” (p. 81). Other studies, however, have hypothesised that the development of proficiency in both L1 and L2 may be less straightforward, highly task-dependent, and modulated by other factors – for example, a high level of language aptitude may allow a particular speaker to acquire and maintain high proficiency levels in both languages (e.g., Cummins, 1991; Bylund et al, 2009; Cherciov, 2013). …”
Section: Investigations Of Development In Both Languagesmentioning
confidence: 99%
“…In that study, the people did not use Ikalanga even in any situations when they were communicating with people with the same mother tongue. Cherciov (2012) reveals that there is not a straight correlation between attitudes and first language attrition through quantitative data measurement but he found prominent connections between the two through qualitative data analysis that was gained through interviews. Many studies of language shift (Schupbach, 2006;Wegmann, 1989) have found that first language shifted at the second generation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researcher found his case very interesting to be investigated in depth. Cherciov (2012) conducted a study to test which methodological approaches, such as C-tests, verbal fluency tasks, sociolinguistic and personal background questionnaires, native speaker ratings, and interviews, are more appropriate for testing the impact of attitude on L1 attrition. She reported that an interview was more flexible in capturing the nuances such as the relationship between emotional factors and language proficiency, whilst a questionnaire-based methodology would give categorized answers, which would not cover in detail the experience of the participant(s).…”
Section: Participantsmentioning
confidence: 99%
“…It often occurs in situations of language contact, for example, in the case of L1 attrition in immigrants living in a foreign country (Cherciov, 2013;Sharwood-Smith, 1989), but there can also be attrition of a foreign language learnt at school and not used any more, that is why in multilingual repertoires the chronological order of language acquisition does not necessarily correspond to language dominance, which is determined by the proficiency levels and the frequency of use of the particular languages (Herdina & Jessner, 2013, p. 754). …”
Section: The Phenomenon Of Language Attritionmentioning
confidence: 99%